CAN HOMEOPATHY BE A "REMEDY" FOR LOSS OF SMELL AND TASTE IN PATIENTS WITH COVID-19? - Onur Tatar; Ulas Serkan Topaloglu; Ali Saz; Mustafa Oner Kucuk; Esma Eryilmaz-Eren (MNJ (Malang Neurology Journal), 2022)
Background: Homeopathy is applied as a supportive in the treatment of viral infections and in relieving their symptoms. Objective: To create an awareness that effective remedial results can be obtained by homeopathy in patients with loss of smell and taste in Coronavirus Disease 2019. Methods: A prospective, cohort and randomized study was conducted. The main inclusion criterion was the loss of smell and taste for at least one week. Homeopathic remedies were also applied as supportive therapy. Visual Analog Scale (VAS) was used to evaluate the loss of smell and taste perception before and after treatment. Results: A total of 30 patients, 32.17±10.25 years, were included in the study. The mean pre-treatment VAS-smell perception of the patients was 0.67±1.24, while the mean VAS-taste perception was 2.57±3.01. After the treatment, the mean of VAS-smell perception was 8.67±1.92, while the mean of VAS-taste increased to 9.43±1.22. There was a strong positive correlation between ΔVAS-smell perception and ΔVAS-taste perception (r: 0.563, p: 0.001). There was also a strong negative correlation between ΔVAS-taste perception and the level of ferritin (r: -0.552, p: 0.002). Conclusion: The present study on the effective improvement via homeopathy treatment in patients with loss of smell and taste in COVID-19 that “has spoiled the taste of life and living” should be supported by further studies.